Strategic enhancement of joint strength in dissimilar Al/Mg alloys: a workable approach for aerospace application - S. Suresh; Elango Natarajan; Kalaimani Markandan; S. Sudhagar; Gnanasambandam Anbuchezhiyan; R. Elayaraja (Discover Materials)
Abstract The increasing importance of dissimilar lightweight metal joints is crucial for advancing aerospace and automotive technologies, where aluminum (Al) and magnesium (Mg) alloys offer an ideal balance of strength and weight. However, the challenges associated with joining these dissimilar metals necessitate innovative solutions. This study explores the role of silicon carbide (SiC) nanoparticles in enhancing the friction stir spot welding (FSSW) of dissimilar alloys AA6061 and AZ31B. The methodology involved varying the rotational speed of the welding tool (1000, 1200, 1400, and 1600 rpm) while keeping other parameters such as plunge depth, plunge rate, and dwell time constant. SiC nanoparticles were introduced through a pre-drilled 2 mm hole at the tool’s plunging point to refine the microstructure and mitigate the formation of brittle Al–Mg intermetallic compounds (IMCs). The addition of SiC nanoparticles modifies the weld microstructure, reducing the formation of brittle Al–Mg IMCs and promoting the development of finer, well-distributed Mg–SiC IMCs, resulting in a more favorable and homogeneous multilayered structure. The incorporation of SiC significantly enhances the strength of the joints, achieving a maximum of 5.68 kN, 22.7% increase compared to SiC-free Al/Mg joints. This improvement underscores potentiality of SiC as a reinforcing element in strengthening dissimilar metal joints and demonstrates the effectiveness of it in dissimilar Al/Mg joints, making them suitable for aerospace and automotive applications.